Utilization of 29Si MAS-NMR to Understand Solid State Diffusion in Energy Storage Materials - Dogan, Fulya; Key, Baris; Vaughey, John T. (Frontiers in Chemical Engineering, 2022)
The properties of many solid-state materials arise from critical interfaces tied to the structure, morphology, and composition of the materials under study. For many materials, identifying components that may be invisible to diffraction techniques or other bulk sensitive techniques (i.e. inductively coupled plasma (ICP)), may cause important information to be overlooked. These can include grain boundary phases, nanoscale coatings, amorphous layers, or second phases that influence the materials environment. In this short review, the use of 29Si MAS NMR as a local probe to detect silicon-containing phases in complex energy storage systems is explored with a focus is on silicon-containing materials and silicon electrodes. Examples highlighting the utility of 29Si MAS NMR include 1) examining copper diffusion into silicon as a method to create 3 dimensional electrodes, 2) using Mg(II) electrolyte additives to create in-situ nanoscale silicide coatings to inhibit low voltage parasitic side reactions and extend calendar life, and 3) studying the lithiation reactions of passivated silicon on different time scales.